Evaluation of the Hospital Information Management System (SIMRS) in the Medical Records Unit Using the Hot-Fit Method at RSUD Welas Asih - Majdi, Faiq Muhammad; Setiatin, Sali; Soelistijaningroem, Matoeari (Jurnal Kesmas Prima Indonesia, 2026)
This study aims to evaluate the effectiveness of the implementation of the Hospital Management Information System (SIMRS) in the Medical Records Unit of Welas Asih Regional Hospital using the HOT-Fit model, which includes the Human, Organization, Technology, and Net Benefit aspects. The research method is a descriptive quantitative survey with a total sampling technique, involving all 41 medical record officers as active SIMRS users. The data collection instrument was a Likert scale questionnaire that has been tested for validity and reliability. Analysis was carried out descriptively by calculating the average value of each component. The results show that the implementation of SIMRS is in the very good category with an overall average value of 4.68. The highest value is found in the Net Benefit aspect, namely 4.73, which confirms that SIMRS provides direct benefits in accelerating service flow and improving data accuracy. The Organization aspect obtained a value of 4.70, Human 4.68, and Technology 4.62, which overall indicate user readiness, organizational support, and system reliability. However, respondents still noted the need to improve network stability and feature development to optimize SIMRS utilization in supporting the medical records service process.